Stop war - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Silk screen print of a traffic STOP sign with the word "WAR" coming out of the bottom of the sign. The image of the word "WAR" is warped and simulates dripping blood.